An international collaborative study to establish the WHO 4th International Standard for Streptokinase: Communication from the SSC of the ISTH. (4th June 2020) - Locke, Matthew; Rigsby, Peter; Longstaff, Colin; ,
Abstract: Streptokinase is used worldwide as a cost‐effective treatment for acute myocardial infarction. Manufacturers use the World Health Organization (WHO) International Standard (IS) for Streptokinase to potency label their products, ensuring consistent, safe, and effective dosing. Stocks of the third IS for streptokinase (coded 00/464) are running low, and an international collaborative study was organized to calibrate a replacement. A total of 15 laboratories from nine countries took part, using chromogenic and/or fibrin clot lysis methods to determine the potency of two candidate preparations, coded 16/356 (sample B) and 16/358 (sample C), relative to the third IS (00/464). A third sample (88/824, sample A), which was used in the collaborative studies to establish the second and third IS, was also included. There was good agreement in potency estimates from different assay methods and low variability both within and between laboratories. Long‐term stability modeling indicated the candidates are very stable. Comparison of potency estimates for 88/824 (sample A) with potencies calculated in previous studies revealed a variability of only 1.9% over the course of three collaborative studies spanning 30 years and more than 50 years of streptokinase standardization. This indicates excellent continuity of the International Unit (IU) and assay methods. Following agreement by study participants and Scientific and Standardization Committee experts of the International Society on Thrombosis and Haemostasis, the WHO Expert Committee on Biological Standardization established 16/358 (sample C) as the fourth IS for Streptokinase with a potency of 1013 IU per ampoule in October 2019.